PENGARUH KEPEMIMPINAN TERHADAP KINERJA PEGAWAI DI DISTRIK AIFAT TIMUR KABUPATEN MAYBRAT - Nany Budi Hardjayanti (Journal of Management Small and Medium Enterprises (SMEs), 2022)
Human resources are one of the most important factors to achieve the goals of an organization. High employee performance can be realized if all elements in the organization are well integrated, and are able to carry out their respective roles. In this study refers to the leadership variable. Employees are the spearhead in an organization, while good employee performance can be seen with one of the important variables, including leadership. The results of the distribution of questionnaires and interviews indicate that employee performance can be achieved optimally, if the communication between the leadership and employees is carried out properly and directed. This study aims to determine the effect of leadership on employee performance in the Aifat District, Middle East, Maybrat Regency. The research method used is interview and sample test. The hypothesis testing tool used is SPSS, t test and simple regression test. The results of hypothesis testing show that leadership has a significant effect, either partially or simultaneously on employee performance. That is, the better the application of leadership, the more optimal the performance of the employees of the Middle East Aifat District, Maybrat Regency will be. Keywords: Human Resources, Leadhership, employee performance